The Effect of Product Innovation and Technology orientation on the Firm Performance. Evidence from the manufacturing Small and Medium Enterprises of Pakistan - Tariq, Tamoor Ali; Lazim, Halim bin Mad; Iteng, Rosman (South Asian Journal of Social Sciences and Humanities, 2021)
Product innovation (PDI) and technology orientation (TO) are well-known dynamic capabilities. Such capabilities aid the firms to cater the customer demand and sustainable growth. Moreover, the performance of manufacturing SMEs in Pakistan yet to receive adequate empirical attention. The theoretical framework for this study is deduce from the dynamic capability view theory. However, current empirical study investigates the relationship between product innovation, technology orientation, and firm performance. The data was collected from 381 manufacturing SMEs of Punjab, Pakistan, and analyzed using PLS-SEM 3.0. The finding of this empirical study suggests that product innovation and technology orientation have positive influence on a firm’s performance.
Keywords: Product innovation; Technology orientation; firm’s performance; Manufacturing SMEs.